Na3V2(PO4)3‐Supported Electrospun Carbon Nanofiber Nonwoven Fabric as Self‐Standing Na‐Ion Cell Cathode. Issue 7 (2nd April 2020) - Meligrana, G.; Ferrari, S.; Lucherini, L.; Celè, J.; Colò, F.; Brugger, J.; Ricciardi, C.; Ruffo, R.; Gerbaldi, C.
Abstract: Sodium‐ion technology is a reliable alternative to lithium‐ion for large‐scale energy storage because of the abundance of sodium sources and related low cost. In this work, we report about a simple fabrication of self‐standing electrodes based on electrospun carbon nanofiber (CNF) loaded with Na3 V2 (PO4 )3 with NASICON framework, which is a promising cathode material that has shown good electrochemical performance when its electrical conductivity is enhanced by a conductive medium. The proposed method is simple, low cost, potentially scalable to fabricate and load cathode support with active materials. The electrochemical tests confirmed the stable cycling performances and the high C‐rate capability of the NVP/CNFs composites, with hundreds of cycles without major degradation of performances. Our work demonstrates that stable, self‐supported, long‐term performing NIB electrodes, ready to use without addition of any performance enhancer, can be obtained by using fast and cost‐efficient procedures suitable to be scaled‐up at an industrial level. Abstract : Stand‐alone cathode : Self‐standing, composite Na‐ion battery cathodes comprising NASICON‐type Na3 V2 (PO4 )3 loaded onto electrospun carbon nanofibers are prepared by simple, low cost, potentially scalable procedure, which is favorable in improving the transport properties of the active material without addition of any performance enhancer; enhanced electrochemical cycling chiefly at high C‐rate is obtained, without major degradation of long‐term performances.